PERAN INTERNAL COMMUNICATION DALAM UPAYA PENCITRAAN PERUSAHAAN (STUDI KASUS PUBLIC RELATIONS PT LIPPO CIKARANG, TBK) - Yuniarti, Tatik (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2012)
Public Relations at a company are required to establish a positive image. Public relations activities include not only the external relations and communications, but only internally. The success of these programs depends on the company's internal communication is conducted by public relations in conveying the message. Internal communications is related to the goals of the organisation and its stage of development. The unit of analysis in this research is Public Relations of PT Lippo Cikarang, Tbk. The aim of research is to analyze internal communication of Public Relations and aspects of consideration from the strategies at PT Lippo Cikarang, Tbk. The methodology applied is qualitative descriptive, aiming to describe the data systematically, factual, and accurately. Data collection was done through indept interview, observation, and documentation from media relations activities by Public Relations of PT Lippo Cikarang, Tbk. The analysis was conducted by using interactive model with Miles and Huberman model consisting of 3 components: data reduction, data display, drawing and verifying conclusions. Internal communications within the company is required to establish a good relationship between employees, between employees and leadership with all stakeholders in the company. Internal communications are conducted by the Public Relations of PT Lippo Cikarang, Inc. proved to be very effective for the success of the activities carried out. Uniformity of all employees on the meaning of a message is the key to creating a good image and reputation to maintain in the public eye externally